Plasma nitriding and nitrocarburising of a supermartensitic stainless steel - Fernandes, F. A P; Totten, G. E.; Gallego, J. [UNESP]; Casteletti, L. C. (Taylor & Francis, 2012)
Supermartensitic stainless steels (SMSSs) are a new generation of the classic 13%Cr martensitic steels, lower in carbon and with additional alloying of nickel and molybdenum offering better weldabilty and low temperature toughness. Several works have shown that plasma nitriding and nitrocarburising of stainless steels at low temperatures produces a hard surface layer which results in increased wear resistance. In this work, SMSS samples were plasma nitrided and nitrocarburised at 400, 450 and 500 °C. The plasma treated SMSS samples were characterised by means of optical microscopy, microhardness, X-ray diffraction and dry wear tests. The thickness of the layers produced increases as temperature is raised, for both plasma nitriding and nitrocarburising. X-ray diffraction demonstrates that the chromium nitride content grows with temperature for nitriding and nitrocarburising, which also showed increasing content of iron and chromium carbides with temperature. After plasma treating, it was found that the wear volume decreases for all temperatures and the wear resistance increased as the treatment temperature was raised. The main wear mechanism observed for both treated and untreated samples was grooving abrasion. © 2012 IHTSE Partnership Published by Maney on behalf of the Partnership.
Keywords: Nitriding; Nitrocarburising; Wear; X-ray diffraction; Chromium carbide; Chromium nitride; Dry wear; Hard surface; Low temperature toughness; Low temperatures; Plasma nitrided; Plasma nitriding; Supermartensitic stainless steels; Treatment temperature; Wear mechanisms; Wear volume; Carbides; Carbonitriding; Chromium; Molybdenum; Nitrides; Nitrogen plasma; Optical microscopy; Plasma applications; Tribology; Wear of materials; Wear resistance; X ray diffraction; Stainless steel